Spatial and Temporal Analysis of Severe Dust Storm in Iraq in May 2022 - Ismail, Rafah Rasheed; Al-Abudi, Bushra Qassim; Halos, Saadiyah H. (Iraqi Journal of Science, 2024)
Dust storms are a common ecological occurrence in many world‘s countries, mainly in dry and semi-dry parts. Dust storms tremendously influence human health, the environment, the climate, and numerous social aspects. In this paper, spatial and temporal analysis, metrological triggers, and trajectory, dust exporting areas of a severe dust storm that occurred in Iraq on May 16, 2022, were investigated. The dust storm’s backward trajectory was determined using HYSPLIT model, which is then compared with MODIS and Meteosat satellite images. The weather is then analyzed using the NCEP/NCAR Reanalysis model, and the approximate area of these sources was determined using Landsat 8 satellite image classification method. The results revealed that the HYSPLIT model trajectory of the dust storm agreed with MODIS and Meteosat satellite visuals. The primary dust storm sources and their areas are identified. The first source is from the shared border region between Syria (Rif-Dimasshq) and Jordan (north of Al-Ruwaished), with an area of about 775 km2. The second is from the northwestern regions of Iraq, specifically north of Anbar and south of Nineveh, with an area of about 905 km2.